Aplikasi Rental Mobil Berbasis Web Studi Kasus pada Adiba Trans Rental menggunakan PHP MySQ - Pelon Wetapo; Herlina Trisnawati (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
The high demand for car rental services in Ciputat, South Tangerang, especially at certain times, has encouraged the growth of many car rental businesses. The presence of many car rental operators in Ciputat certainly creates fierce competition between them. Therefore, it is important for these businesses to carry out continuous evaluation and development in order to remain competitive with competitors. Success in providing satisfactory service to customers will make them remain loyal to using their favorite rental services. Conclusions and recommendations from the study conducted related to Web-Based Car Rental Applications in the Adiba Trans Rental Case, which was built using PHP and MySQL. The results of this study indicate that the development of a web-based application for car rental in the Adiba Trans Rental case using PHP and MySQL has succeeded in meeting the expected objectives. This application offers an effective solution for managing car rentals with ease of use via the web. The effectiveness of this application can be seen from its complete functional capabilities, easy-to-use user interface, and smooth integration between PHP as a programming language and MySQL as a database management system.